Mechanisms sensing and modulating signals arising from cell swelling - Jakab, Martin; Fürst, Johannes; Gschwentner, Martin; Bottà, Guido; Garavaglia, Maria-Lisa; Bazzini, Claudia; Rodighiero, Simona; Meyer, Giuliano; Eichmueller, Sonja; Wöll, Eichmüller; Chwatal, Sabine; Ritter, Markus; et al. (Cellular physiology and biochemistry, 2002)
Cell volume alterations are involved in numerous cellular events like epithelial transport, metabolic processes, hormone secretion, cell migration, proliferation and apoptosis. Above all it is a need for every cell to counteract osmotic cell swelling in order to avoid cell damage. The defence against excess cell swelling is accomplished by a reduction of the intracellular osmolarity by release of organic- or inorganic osmolytes from the cell or by synthesis of osmotically less active macromolecules from their specific subunits. De-spite the large amount of experimental data that has accumulated, the intracellular mechanisms underlying the sensing of cell volume perturbations and the activation of volume compensatory processes, commonly summarized as regulatory volume decrease (RVD), are still only partly revealed. Moving into this field opens a complex scenario of molecular rearrangements and interactions involving intracellular messengers such as calcium, phosphoinositides and inositolphosphates as well as phosphoryla-tion/dephosphorylation processes and cytoskeletal reorganization with marked cell type- and tissue specific variations. Even in one and the same cell type significant differences regarding the activated pathways during RVD may be evident. This makes it virtually im-possible to unambigously define common sensing- and sinaling pathways used by differ-ent cells to readjust their celll volume, even if all these pathways converge to the activa-tion of comparatively few sets of effectors serving for osmolyte extrusion, including ion channels and transporters. This review is aimed at providing an insight into the manifold cellular mechanisms and alterations occuring during cell swelling and RVD.